Glutamine metabolism modulates azole susceptibility in trypanosoma cruzi amastigotes - Dumoulin, Peter C.; Vollrath, Joshua; Tomko, Sheena Shah; Wang, Jennifer X; Burleigh, Barbara (eLife, 2020)
The mechanisms underlying resistance of the Chagas disease parasite, Trypanosoma cruzi, to current therapies are not well understood, including the role of metabolic heterogeneity. We found that limiting exogenous glutamine protects actively dividing amastigotes from ergosterol biosynthesis inhibitors (azoles), independent of parasite growth rate. The antiparasitic properties of azoles are derived from inhibition of lanosterol 14α-demethylase (CYP51) in the endogenous sterol synthesis pathway. We find that carbons from 13C-glutamine feed into amastigote sterols and into metabolic intermediates that accumulate upon CYP51 inhibition. Incorporation of 13C-glutamine into endogenously synthesized sterols is increased with BPTES treatment, an inhibitor of host glutamine metabolism that sensitizes amastigotes to azoles. Similarly, amastigotes are re-sensitized to azoles following addition of metabolites upstream of CYP51, raising the possibility that flux through the sterol synthesis pathway is a determinant of sensitivity to azoles and highlighting the potential role for metabolic heterogeneity in recalcitrant T. cruzi infection.
Gesehen am 04.02.2021